DESIGN OF AN ELECTROMECHANICAL FACILITY FOR A GAS CENTER - Martínez Silva, Luis (2004)
is article deals about the design of an electromechanical facility for a Gas Center, that includes two parts: Electrical facilities and mechanical facilities. Aspects such as process design, equipment distribution, security and legal requirements are analized in both of them, with the purpose of proposing the design for installing a gas center that can help diminish environmental pollution.